The effects of a cluster-randomized control trial manipulating exercise goal content and planning on physical activity among low-active adolescents - Tessier, Damien; Nicaise, Virginie; Sarrazin, Philippe (Frontiers in Psychology, 2022)
The purpose of the main trial (study 2) compared the effect of intrinsic and extrinsic-goal framing messages alongside planning (IMC+P and EMC+P) to a control condition (CC) on low-active adolescents’ physical activity (PA), intention, attitude, and exercise goals, and examined the potential mediational effect of these variables within the PA change process. Low-active students (n=193; Mage = 16.89) from fifteen classes were assigned to one of these three conditions. PA was assessed using an accelerometer, and the socio-cognitive mediators were measured at baseline (i.e., two weeks before the intervention) and post-test, and the intention was measured again at follow-up (i.e., two weeks after the intervention). Results showed that compared to adolescents in the CC group, those in the experimental conditions did not do more moderate PA, but carried out more light PA, and yielded an increase in attitude and intention. Mediational analysis revealed no significant effect of the potential mediators.